Comparison of Ego Strength, Aggression, and Fear of Loss in Three Groups with Anxiety Symptoms, Depression Symptoms, and Normal Individuals - Razaghi, Zahra; Hojjati, Atefeh (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: This study was conducted with the aim of comparing ego strength, aggression, and fear of loss among three groups: individuals with anxiety symptoms, individuals with depression symptoms, and normal individuals.Methods and Materials: The research design was a causal-comparative method. The statistical population of this study included all women aged 20-40 years who referred to counseling centers in the province of Qom. The sample consisted of 105 women aged 20-40 years who referred to counseling centers in the province of Qom and were selected using convenience sampling. The instruments used in this study included the Beck Depression Inventory (second edition), the Beck Anxiety Inventory, the Ego Strength Psychological Questionnaire by Markstrom et al., the Fear of Loss Questionnaire by Przybylski, and the Buss-Perry Aggression Questionnaire. To analyze the findings, both univariate and multivariate analysis of variance (ANOVA) were used, and data analysis was conducted using SPSS.26 software.Findings: The results showed that the normal group had higher ego strength compared to the groups with depression and anxiety symptoms. The group with depression symptoms exhibited a higher fear of loss compared to the anxiety symptoms group and the normal group, and aggression was higher in the anxiety symptoms group compared to the depression symptoms group and the normal group (p < .01).Conclusion: The study concludes that ego strength, aggression, and fear of loss significantly differ among individuals with anxiety symptoms, depression symptoms, and normal individuals. Higher ego strength was observed in the normal group, while the depression group exhibited greater fear of loss, and aggression was most pronounced in the anxiety group.